Cartera vencida de la Empresa Bell Novainser correspondiente al año 2020-2021. - Miranda Beldox, Graciela Cristina (2022)
This research work deals with the management of the overdue portfolio of the company BellNovainser, whose line of business is the sale of computer equipment, appliances and technology. In addition to the technical service, it is a company that provides lines of credit to both natural and legal persons. During the pandemic due to COVID 19, a good part of the clients fell into arrears due to the economic recession, this situation affects everyone. The collection management area was faced with a situation never seen before. As mobility and capacity restrictions were very harsh, the extensions in Quevedo and Ventanas were closed, leaving 3 stores in Babahoyo and 1 in Montalvo. The closing of the Quevedo store meant the increase of a portfolio worth $12,300 dollars corresponding to the clients of that city. The company BELLNOVAINSER has managed to handle this stage of difficulties, however there is a portfolio that must be recovered. The credit area, together with the collection area, has implemented systems that allow not only the recovery of the overdue portfolio but also to retain the client once their income has stabilized. Clients can access discounts on interest, discounts for debt settlement and a new line of credit. Managing an adequate policy when opening a line of credit minimizes the risk of overdue portfolio, allows establishing healthy business relationships and provides benefits to both parties.